Photonic neuromorphic information processing and reservoir computing - Lugnan, A.; Katumba, A.; Laporte, F.; Freiberger, M.; Sackesyn, S.; Ma, C.; Gooskens, E.; Dambre, J.; Bienstman, P. (APL Photonics, 2020)
Photonic neuromorphic computing is attracting tremendous research interest now, catalyzed in no small part by the rise of deep learning in many applications. In this paper, we will review some of the exciting work that has been going in this area and then focus on one particular technology, namely, photonic reservoir computing.
Keywords: Photonic neuromorphic; Information processing; Reservoir computing